Episodic Cancer Pain: Patient Reporting, Prevalence, and Clinicodemographic Associations at Initial Cancer Pain Clinic Assessment - Paulo Reis-Pina; Anand Acharya; Antonio Barbosa; Peter G. Lawlor (Pain Research and Management)
Background. Better understanding of the episodic cancer pain (CP) spectrum, including pains that occur in addition to its conventionally defined breakthrough CP (BTcP) and incident CP (IcP) components, may inform CP assessment and management. This study aimed to determine the prevalence of episodic patient-reported CP and the prevalence and associations of study-defined BTcP (S-BTcP) and IcP (S-IcP) in patients with CP. Methods. In a cross-sectional study at their first CP clinic attendance, participants with CP had the following assessments: Brief Pain Inventory (BPI); Pain Management Index (PMI), with PMI-negative status indicating undertreatment; standardized neuropathic pain component (NPC) status; S-BTcP (no trigger identified) and S-IcP (trigger identified) status, based on a preceding 7-day history of transitory pain flares distinct from background pain, and BPI-Worst or BPI-Now pain intensity ≥ 4. Clinicodemographic variables’ association with S-BTcP and S-IcP was examined in logistic regression analyses. Results. Of 371 participants, 308 (83%) had episodic CP by history alone; 140 (37.7%) and 181 (48.8%) had S-BTcP and S-IcP, respectively. Multivariable analyses demonstrated significant (p<0.05) associations (odds ratios: 95% CIs) for 6 variables with S-BTcP: head and neck pain location (2.53; 1.20–5.37), NPC (2.39; 1.34–4.26), BPI average pain (1.64; 1.36–1.99), abdominal pain (0.324; 0.120–0.873), S-IcP (0.207; 0.116–0.369), and PMI-negative status (0.443; 0.213–0.918). Similar independent associations (p<0.05) occurred for S-IcP with NPC, BPI average pain, and PMI-negative status, in addition to radiotherapy, S-BTcP, soft tissue pain, and sleep interference. Conclusions. Episodic or transient patient-reported CP flares often do not meet the more conventional criteria that define BTcP and IcP, the principal episodic CP types. Both BTcP and IcP occur frequently and both are associated with a NPC, higher pain intensity, and less opioid underuse in the management of CP. Further studies are warranted to both better understand the complex presentations of episodic CP and inform its classification.